Factors Related to Incidence of Mallnutrition in Children Under Five in Wee Kombaka Village Southwest Sumba District - Ate, Piteryanus; Talahatu, Anna Heny; Limbu, Ribka (Faculty of Public Health, Nusa Cendana University, 2022)
Malnutrition is a lack of nutrients which include protein, carbohydrates, fats and vitamins that the body needs. Southwest Sumba Regency in 2018 there were cases of malnutrition in 13 sub-districts of the Puskesmas working area. Wee Kombaka Public Health Center is one of the health centers with 45 cases of malnutrition. Wee Kombaka Village is the working area of ​​Wee Kombaka Health Center with 45 cases of malnutrition. The purpose of this research is to analyze the factors related to the incidence of malnutrition in children under five in Wee Kombaka Village, Southwest Sumba Regency 2021. The type of research used is analytical research with a cross sectional study method. The sample used in this research is 53 people. The data analyzed using Chi-square with a significance level of = 0.05. Research shows all variables related to the incidence of malnutrition in children under five, namely the mother's level of knowledge (p-value = 0.006), attitude (p-value = 0.004), action (p-value = 0.004) and history of exclusive breastfeeding (p-value = 0.002). The conclusion in this research is that there is a relationship between knowledge, attitudes, actions and history of exclusive breastfeeding on undernourished children under five, therefore the community, especially mothers of toddlers, are expected to pay more attention to the sources and types of food for toddlers as well as the processing process to serving food to children